Diabetic peripheral neuropathy in ambulatory patients with type 2 diabetes in a general hospital in a middle income country: a cross-sectional study. - María de Los Angeles Lazo; Antonio Bernabé-Ortiz; Miguel E Pinto; Ray Ticse; German Malaga; Katherine Sacksteder; J Jaime Miranda; Robert H Gilman (PLoS ONE)
Aim We aimed to estimate the morbidity rate and associated factors for diabetic peripheral neuropathy (DPN) in a low-middle income country setting. Methods Cross-sectional study, data was gathered at Peru's Ministry of Health national specialized hospital for endocrinological conditions through standardized interviews, anthropometric measurements and blood tests for glycated haemoglobin (HbA1c). DPN was evaluated using two techniques: the Semmes-Weinstein monofilament test and the diabetic neuropathy symptom score. Overall prevalence and 95% confidence intervals (95% CI) were calculated. Potential factors related to DPN explored included body mass index, years with disease (<10 vs. ≥10 years), glycaemic control (HbA1c <7% vs. ≥7%), microalbuminuria, retinopathy, and current pharmacological treatment. Multivariable analysis was performed using Poisson analysis to calculate prevalence ratios. Results DPN was observed in 73/129 (56.6%) patients. In multivariable analysis adjusted by age and sex, the prevalence ratio of neuropathy was 1.4 times higher (95% CI 1.07-1.88) in patients who took insulin plus metformin compared to patients who used one treatment alone, and 1.4 higher (95% CI 1.02-1.93) in patients with ≥10 years of disease compared to those with a shorter duration of disease. Also we found some characteristics in foot evaluation associated to neuropathy such as deformities (p<0.001), onychomycosis (p = 0.012), abnormal Achilles reflex (p<0.001), pain perception (p<0.001) and vibration perception (p<0.001). Conclusion DPN is highly frequent among patients with diabetes in a national specialized facility from Peru. Associated factors to DPN included being a diabetic patient for over ten years, and receiving insulin plus metformin.